PENYIMPANGAN PERILAKU SEKSUAL (MENELAAH MARAKNYA FENOMENA LGBT DI INDONESIA) - Saidah, Elbina Mamla (AL-ISHLAH: Jurnal Pendidikan, 2016)
The phenomenon of LGBT (Lesbian, Gay, Bisexual, and Transgender) makes people very worried. Pros and cons of the LGBT happen in the mass media; print media and electronic media. In medical science, there are four major categories of mental disorder diagnosis, namely: gender identity disorder, sexual deviation, psychosexual dysfunction, and other psychosexual disorders such as homosexuals. The LGBT issue should get a good handle on all aspect, especially the family. Parenting and monitoring the development of children from infancy to adolescence need to be improved so that children develop well.